Complement Factor B Is a Determinant of Both Metabolic and Cardiovascular Features of Metabolic Syndrome. Issue 3 (September 2017) - Coan, Philip M.; Barrier, Marjorie; Alfazema, Neza; Carter, Roderick N.; Marion de Procé, Sophie; Dopico, Xaquin C.; Garcia Diaz, Ana; Thomson, Adrian; Jackson-Jones, Lucy H.; Moyon, Ben; Webster, Zoe; Ross, David; et al.
Abstract : CFB (complement factor B) is elevated in adipose tissue and serum from patients with type 2 diabetes mellitus and cardiovascular disease, but the causal relationship to disease pathogenesis is unclear. Cfb is also elevated in adipose tissue and serum of the spontaneously hypertensive rat, a well-characterized model of metabolic syndrome. To establish the role of CFB in metabolic syndrome, we knocked out the Cfb gene in the spontaneously hypertensive rat. Cfb −/− rats showed improved glucose tolerance and insulin sensitivity, redistribution of visceral to subcutaneous fat, increased adipocyte mitochondrial respiration, and marked changes in gene expression. Cfb −/− rats also had lower blood pressure, increased ejection fraction and fractional shortening, and reduced left ventricular mass. These changes in metabolism and gene expression, in adipose tissue and left ventricle, suggest new adipose tissue-intrinsic and blood pressure-independent mechanisms for insulin resistance and cardiac hypertrophy in the spontaneously hypertensive rat. In silico analysis of the human CFB locus revealed 2 cis -regulated expression quantitative trait loci for CFB expression significantly associated with visceral fat, circulating triglycerides and hypertension in genome-wide association studies. Together, these data demonstrate a key role for CFB in the development of spontaneously hypertensive rat metabolic syndrome phenotypes and of related traits in humans and indicate the potential for CFB as a novel target for treatment of cardiometabolic disease. Abstract : Supplemental Digital Content is available in the text.